СРАВНИТЕЛЬНЫЙ АНАЛИЗ АМИНОКИСЛОТНЫХ ПОСЛЕДОВАТЕЛЬНОСТЕЙ БЕЛКОВ ТРАНСПОРТА ЦИНКА В КЛЕТКАХ БАКТЕРИЙ РОДА Pseudomonas (Experimental biology, 2009)
Bacteria of Pseudomonas aeruginosa sp., resistant to high concentration of zinc ions were isolated from active silt. The paper presents the evaluation of the degree of homology, analysis of conserved domains of protein transportsystem of zinc ions the cells of bacteria of the genus Pseudomonas.
Keywords: Pseudomonas